Planning local economic development - "Blakely , Edward J." (New Delhi, 1989)
The new edition of this major book continues to explore theories of local economic development that are relevant to dilemmas facing communities today. It expands upon issues such as the planning process, analytical techniques, business and human resource development and investigates new areas such as high technology economic development strategies.
Keywords: Industrial promotion -United State